Diagnostic role of Ultrasonography in acute appendicitis (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Abdominal Ultrasonography (USG) is the most commonly used method for diagnosing acute appendicitis the most common surgical cause of acute abdomen. In this study, we observed the reliability of USG for diagnosing acute appendicitis. Objectives: To evaluate the role of ultrasonography in the diagnosis of acute appendicitis. Methods: In this study, we performed abdominal USG of 100 patients admitted with lower right abdominal pain and diagnosed as acute surgical abdomen according to the physical examination and laboratory findings. These patients were surgically treated by appendecectomy, and excised specimens were sent for histopathological examination. Results: One hundred patients were assessed in this study. Out of them 82.0% patients had acute appendicitis and diameter of their appendices were more or equal to 6 mm. Twenty nine percent of the patients were below 21 years of age. Intraluminal fluid was present in 81% of patients and peri-appendicular fluid was present in 66.7% of patients. Leucocytosis was present in 49% of the cases and neutrophilia in 84% of the cases. All of the patients presented with lower abdominal pain with migration of pain in 52% cases and they had right iliac fossa tenderness. The sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and accuracy rate of ultrasonography was 76.8%, 88.9%, 96.9%, 45.7% and 79.0%, respectively. 45 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Conclusion: Acute appendicitis is a common indication for emergency abdominal surgery. Proper clinical assessment is the mainstay of diagnosis in acute appendicitis and addition of routine abdominal ultrasound by graded compression technique can improve the diagnostic accuracy and adverse outcome. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22904 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014